ANALISIS FAKTOR-FAKTOR PEMBENTUK NIAT KONSUMEN MENGIKUTI ARISAN KUE LEBARAN - Yuni Firayanti; Ahmadi; Siti Komaria; Natasha Armanda (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
The purpose of this research is to know the characteristic of consumers and the factors that form consumers intentions to participate arisan kue lebaran. This research is an explanatory approach by distributing a questionnaire of 74 respondents. The characteristics of the respondents in this study were dominated by women aged 18-25 years. The data analysis technique used is actor analysis (Explanatory Factor Analysis). The results showed that there were 23 variables forming consumers intention to participate arisan kue lebaran which could be grouped into ive actors, namely marketing stimulus, social actors, attitude toward arisan kue lebaran, perceived motivation adn behavioral control and personal characteristic. The results of this study still need to be continued with a conirmatory approach so that it is stronger in explaining the formation o consumer intentions in participating arisan kue lebaran..